Innovative Methods of Teaching Future Teachers - Kholikov Jassurbek Khakimjon oglu; Tojiev Khakimjon Khalikovich (Zien Journals, 2022)
This article describes in detail the innovative conditions created in the training of future teachers, opportunities to support them and opportunities in the educational system
Keywords: national program; Education; training Staff training; creativity